EKSPLORASI TEKNIK LASER CUT DAN RUFFLE PADA BUSANA AVANT-GARDE FUTURISTIK DENGAN SUMBER IDE HUA MULAN - Rindu Pradita Nastiti; Irma Russanti (Kampus Akademik Publiser, 2026)
This research explores the design of futuristic Avant-Garde fashion inspired by the legend of Hua Mulan, utilizing experimental laser-cutting technology and fabric ruffle manipulation. Employing a design development methodology frameworked within the Double Diamond schema, the creation process systematically encompassed four stages: discover, define, develop, and deliver. The product quality assessment involved expert respondents through a structured observation method, with the data analyzed via descriptive quantitative techniques based on mean score calculations. The technical and aesthetic evaluation parameters focused on laser-cut precision, stacked ruffle volume, the visual interpretation of the Hua Mulan theme, and the distinctiveness of the Avant-Garde character. The research findings demonstrated the design's success, with the mean scores per indicator ranging from 3.33 to 4.00. This high cumulative score indicates that the resulting garments received a highly favorable response and successfully met the eligibility standards for scientific publication.